Surface and intra-pulpal temperature variation during tooth whitening photoactivated with LED/laser - Costa, Joatan Lucas de Sousa Gomes (2023)
This study evaluated the variation of surface and intra-pulpal temperature, during bleaching protocol, using LED/laser. The 35% (HP35), 15% (HP15) and 6% (HP6) gels were used associated with LED/laser applied every 1 min for 30 min in a human canine. The evaluation of surface temperature variation (∆Ts) was performed using a pHmeter and the intra-pulpal temperature variation (∆Ti) was performed using a digital thermometer, at times of 1-, 5-, 10-15-and 30-min. Statistical analysis was performed using the two-way repeated measures ANOVA test and Bonferroni post-hoc test was used at a significance level of 5%. HP35 and HP15 showed greater temperature variation than HP6 up to 10 min of surface evaluation, showing no differences between them. In the intra-pulpal evaluation, no group showed differences throughout the procedure.